Analisis Pengaruh Corporate Governance Terhadap Kinerja Keuangan Dengan Manajemen Laba Sebagai Variabel Moderasi - Agus Setiyawan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The main objective of this research is to examining corporate governance and earning managements as a moderation variable effect on financial performance with the control variable size and growth. The financial performance is measured by using a Return on Assets and for profit management measured using the Modified Jones Model and for corporate governance is measured by: institutional ownership, managerial ownership, the proportion of independent board and the board of commissioners. The population in this research is manufacturing companies listed in Indonesia Stock Exchange during the period 2013 - 2015 with the overall number of 342 samples data from 114 companies over three years. The results show that institutional ownership has an significant positive effect on financial performance, managerial ownership has not effect on financial performance, proportion of independent board of commissioners has an significant positive effect on financial performance, board of commissioners has not effect on financial performance. Earning management has not manage effect moderate corporate governance on financial performance.